Sustainable Education to Promote Inclusion in Gifted Children throughout Socialization, after COVID-19 Pandemic - Martina Brazzolotto (Pensa MultiMedia, 2022)
Sustainable education promotes certain values such as: equity, respect, tolerance and inclusion, ideals that develop through social interactions. Our study investigated socialization in gifted children, after the covid-19 pandemic, to understand if some values of sustainable education are transmitted and if the presence or lack of such values can affect school and social inclusion. If before the pandemic the socialization of gifted children was compromised mainly due to their asynchronous development (Columbus group, 1991; Cross, 2015;), during the pandemic socialization was penalized by isolation, the decrease in interactions and the conflict experienced in the family (Aboud, 2021; Türksoy & Karabulut, 2020). In our small study, we created an online questionnaire based on some items from the ICF-CY (2007), that it was compiled by 21 parents of gifted children. The results show that gifted children, after the pandemic, struggle to express emotions; furthermore, there would be a renewed tendency towards isolation during conflict management; constant derision by peers for the special interests of the gifted. Values such as respect, acceptance of the unexpected and self-awareness of excesses would be in line with sustainable education. The implications for teaching are discussed in the article.